2022
DOI: 10.1186/s42238-022-00149-6
|View full text |Cite
|
Sign up to set email alerts
|

Watching the grass grow: does recreational cannabis legalization affect retail and agricultural wages?

Abstract: Background Over the past several years, cannabis has become legal for recreational use in many US states and jurisdictions around the world. The opening of these markets has led to the establishment of hundreds of cannabis production and retail firms with accompanying demand for labor, leading to concerns about spillover effects on wages from incumbents. Methods We study the markets for agricultural and retail labor in Washington and Colorado from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Marijuana legalization's impact has been extensively studied across disciplines. These include health (Raman & Bradford, 2022; Sarvet et al., 2018), crime or substance abuse (Sabia et al., 2021; Wu et al., 2021), as well as income (Chakraborty et al., 2020; Dave et al., 2023; Jiang & Miller, 2022). Others have shown that students value some college amenities (i.e., student activities and sports) resulting in positive or negative effects on achievements (Jacob et al., 2018; Lindo et al., 2012; Webber & Ehrenberg, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Marijuana legalization's impact has been extensively studied across disciplines. These include health (Raman & Bradford, 2022; Sarvet et al., 2018), crime or substance abuse (Sabia et al., 2021; Wu et al., 2021), as well as income (Chakraborty et al., 2020; Dave et al., 2023; Jiang & Miller, 2022). Others have shown that students value some college amenities (i.e., student activities and sports) resulting in positive or negative effects on achievements (Jacob et al., 2018; Lindo et al., 2012; Webber & Ehrenberg, 2010).…”
Section: Introductionmentioning
confidence: 99%